Analisis Implementasi Musyarakah bagi UMKM pada Era Ekonomi Digital: Peluang, Tantangan Regulasi, dan Strategi Penguatan - Abdulloh Wasian; Nazzid Abdullah Haiyi; Umar Maulana; Muhammad Farid Anaqi; Muhammad Yoga Nur Adwitya Zain; Wahyu Aji Satrio; Ridho Arifianto; Taufiq Kurniawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research discusses the application of musyarakah contracts as a sharia financing solution for Micro, Small and Medium Enterprises (MSMEs) in the midst of digital economic development. MSMEs have a crucial role in sustaining the Indonesian economy, but still experience difficulties in accessing fair and sustainable financing. The musyarakah agreement, with its partnership and profit-sharing principles, is considered to be in line with the character of MSMEs that prioritize cooperation and justice. Through a qualitative approach based on a literature study, this research explores the potential, regulatory challenges, and strategies to strengthen the implementation of digital musyarakah. The results of the analysis show that digitalization offers great opportunities in promoting Islamic financial inclusion, but is still constrained by low digital literacy, limited infrastructure, and weak supervision of sharia principles. Therefore, a strategy is needed that includes improving education, developing Islamic financial technology, and collaboration between regulators, financial service providers, and MSME players. This study concludes that the successful implementation of digital musyarakah requires an integrated approach so that MSMEs are able to access Islamic financing independently, fairly and sustainably.